SOSIALISASI PENGAJARAN KOSA KATA BAHASA INGGRIS DI SEKOLAH DASAR DENGAN MENGGUNAKAN VIDEO PENGAJARAN DI SDN 03 ANDURING KOTA PADANG ” - Hevriani Sevrika; Elmiati Elmiati (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
Teaching English is highly recommended to be introduced to students at an early age, this aims to familiarize and train students' tongues or pronunciation organs of English letters and words. Besides that, children are good memorizers and reminders, so they will very quickly memorize and remember something they have just learned. The implementation of the independent curriculum brought back English subjects to elementary school students. As a starting point, English will only be taught to grade 1 and 6 elementary school students according to the implementation of the independent curriculum. To carry out this program, of course schools must be prepared with teacher resources as the initial capital for implementing English teaching apart from school facilities. It is not difficult to find English teachers who are in accordance with their fields because there are so many teachers who have graduated from the English Education Department. The students at SDN 03 Anduring, Padang City, are very active and very happy with learning English through video media. This is because, students are invited to actively use vocabulary with interesting teaching videos. By holding this service activity, it provides enthusiasm and motivation for elementary school teachers to be able to teach English with video media which is the result of the work of the English teachers themselves. This service will be carried out at the English Teacher Working Group (KKG) in Kuranji District which is based at SDN. 03. Anduring City of Padang. At the end of this activity, it is hoped that the teacher will get useful information about how to teach English to elementary school students and the lessons presented to students will be more varied.